The fix [compact disc, abridged] - Baldacci, David (Baldacci, David. Amos Decker series., 2017)
Amos Decker investigates a murder-suicide that occurred outside FBI headquarters and cannot connect the shooter and his victim, but he is ordered off the case, and it becomes clear that finding the link is a matter of national security.